Development of self-healing vanillin/PEI hydrogels for tissue engineering. (20th April 2023) - Yasar, Merve; Oktay, Burcu; Dal Yontem, Fulya; Haciosmanoglu Aldogan, Ebru; Kayaman Apohan, Nilhan
Graphical abstract: Highlights: Vanillin is methacrylate functionalized with 2-isocyanatoethyl methacrylate and used as a bio-based cross-linker for UV-induced bonding and Schiff-base bonding. UV polymerized hydrogels also have a self-healing ability to form a Schiff-base reaction between the amine group of PEI and the aldehyde group of vanillin. The mechanical properties showed that the self-healed hydrogels are just efficient as the originals. The MTT test revealed that hydrogels were non-cytotoxic and supported cell adhesion. Abstract: Self-healing materials recover mechanical damages to expand the lifetime of the material provided. In this study, self-healing hydrogels have been successfully prepared using a novel and simple technique. Vanillin is a natural monomer, used as a bio-based cross-linker for UV-induced bonding and Schiff-base bonding. Methacrylate-functionalized vanillin (M-VAN) is covalently integrated with the polymer matrix. While M-VAN supports polymer matrix with its vinyl group, its aldehyde functionality helps the formation of dynamic covalent imine bonds via Schiff-base formation. The hydrogel showed excellent self-healing ability overnight under physiological conditions without external addition. In addition, the hydrogel surface was modified by collagen and its cell viability was investigated. The prepared scaffolds showed good cell viability of 124% and 163% compared to the control sample. The developed self-healing material reveals that it has possible uses for future biomedical applications and tissue engineering studies due to the self-healing mechanism taking place under ambient conditions.